Les mouvements coopératifs dans les hautes terres de l'Ouest-Cameroun - Albert Jiotsa; Timothy Musima Okia; Henri Yambene (Revue de Géographie Alpine)
Cooperative societies in the Western Highlands (West and North West regions) of Cameroon is an age old institution which started with the arrival of the European colonialists towards the end of the nineteenth century. The fertile soils of this region favors agricultural activities thereby giving rise to many cooperatives in the region. The cooperative societies that have been developed in these areas are the type found in sub Saharan Africa which has stood the test of time more than half a century whereby the other cooperatives elsewhere in the same country have failed. The question this article is about to provide answers is to what has made these cooperatives in the Western Highlands of Cameroon able to stand the test of time when others are quitting the scene. To come out with this scientific article we have implored the active participatory research methodology. The analysis shows that these cooperatives since their creation have been imploring certain innovative measures to make them adapt to the many constraints in their sector.